Exploiting the stress response to radiation to sensitize poorly immunogenic tumors to anti-CTLA-4 treatment - Demaria, Sandra (Landes Bioscience, 2013)
Radiotherapy sensitizes unresponsive tumors to the antineoplastic activity of antibodies that target the inhibitory receptor CTLA-4 on T cells. One molecular mechanism accounting for this therapeutic synergy is the induction of NKG2D ligands on irradiated tumor cells. The fact that NKG2D receptors must be engaged for the elicitation of CD8(+) T-cell antitumor responses has important clinical implications.